PROSEDUR STANDAR OPERASIONAL PEMESANAN PAKET WISATA PELAYARAN DI LE PIRATE EXPLORE CRUISE-LABUAN BAJO - Tettie Setiyarti; Ni Putu Eka Safitri; Pipit Sundari (Forum Manajemen, 2022)
When serving guests, the Reservation Department of a shipping company must be provided with guidelines, work references (sequence), and training in providing services. All forms of work guidelines and references are then referred to as Standard Operating Procedures (hereinafter abbreviated as SOP). On this article, based on the research that has been carried out, the author wants to explain in more detail, using a qualitative descriptive research method, regarding the SOP of the Reservation Department at Le Pirate Explore Cruise – Labuan Bajo. The research that forms the basis of this article was carried out in the first and second quarters of 2021, at a time when Bali and East Nusa Tenggara had not yet fully opened their tourism activities. Based on the findings, the research divides the process of implementing the Standard Operating Procedures (SOP) of the Reservation Department into three main thematic, namely: 1) the role of the Owner in making and supervising PSO Reservations; 2) Reservation Department staff behavior; and 3) obstacles faced by the Reservation Department in implementing PSO.